The road to conscious machines: AI through failed ideas - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2021)
Presented here is a review of the book by Michael Wooldridge The Road to Conscious Machines: The Story of AI. The book was published in 2021 by Pelican Publishing Company. The book presents a philosophical exploration of the AI-related quest to understand the essence of our minds, ethics, and consciousness. Nonetheless, the book is unconventional as it focuses on failures of past AI programs rather than on AI success stories. The author also indicates the possible pathways to develop new, more efficient AI paradigms. The short technical section at the end of the book offers more in-depth information on topics like Prolog, Bayesian, and deep neural networks.